Trends in plant tissue culture and biotechnology - Pareek, L. K.; Swarnkar, P. L. (Bikaner : Agro Botanical Publishers, 1997)
Papers presented at a symposium held in 1994 at Jaipur.
Includes bibliographical references (p. 321-334).
Keywords: Plant tissue culture -- Congresses; Plant biotechnology -- Congresses